Solitary Wave Solutions for Time-Fractional Dispersive LongWave Equations via Generalized Kudryashov-Auxaliry Method - Gaber, A. A. (Communications in Mathematics and Applications, 2021)
In this paper, we present Generalized Kudryashov-Jacobian Method (GKJM) to obtain new type of general exact solutions for nonlinear partial differential equations. GKJM is applied to time-fractional dispersive long wave equations. Seven types solutions of this equation are obtained and including trigonometric function and hyperbolic function. The obtained solutions represent kink wave, anti-kink wave, singular wave, and periodic wave.